SESSION "CLASSICAL PHILOLOGY, BYZANTINE AND MODERN GREEK PHILOLOGY OF THE COUNCIL ON PHILOLOGY EMA (Moscow, January 15-17, 2014) (Proceedings of Southern Federal University. Philology, 2014)
Grigoriyan E.L.Keywords: philology, Byzantine philology, modern Greek philology, urgency, Philology Council.The article is devoted to the meetings of the section «Classical Philology, Byzantine and modern Greek Philology» of the Philology Council of EMA, which was held in Moscow in January, 2014. The author describes in detail all three days of sessions and briefly analyzes the reports which were presented there. One of the interesting facts of the meetings, in the author’s opinion, was that in addition to the reports and round-table discussions, the reference was made to the topics of the graduation works of students, which were related to the topic of the meetings. This demonstrates the interest and relevance of the conference theme.